Brundibár – A Children’s Opera: History and Present - Pirníková Tatiana (Slovenské divadlo)
The paper focuses on the opera Brundibár. The authorial couple – composer Hans Krasa and librettist Adolf Hoffmeister – wrote it in the period of growing interest of artists in pedagogical aspects of the works of art. The changed social climate, however, meant for the work an unplanned journey – during the Second World War it was performed inside the Terezin ghetto by its inhabitants. The human message of the fairy tale story has thus been elevated into a higher symbolic frame – a resistance against the arrogance of power and violence. Especially the post-war era followed this symbolism. The author of the paper contemplates the innovative interpretative levels whose ambition is to cross the traditional performance frame of the work and to find connections with problems of contemporary society.